Employee Performance Affects the Compensation Provided by the Company - Calvin Adam Koljaan; Dedi Rianto Rahadi (International Journal of Business Studies, 2022)
This research aims to understand the effect of compensation given by the company to employees for work motivation. motivation on employee performance and to determine the effect of job satisfaction on employee performance at PT Takagi Sari Multi. This research uses online questions to employees of PT. takagi sari multi. The research method used is quantitative and qualitative research methods. According to the research results, it is found that compensation has a very positive effect on employee job satisfaction, motivation has a positive and significant effect on job satisfaction, which is one of the compensation factors in the company. Based on the research results, the company PT. It is recommended that Takagi Sari Multi Utama balance fairly with their respective performance, all research subjects who are the results of qualitative and quantitative measurements or calculations regarding certain characteristics of all complete and clear group members whose benefits will be studied.